2022
DOI: 10.3389/fhort.2022.1091342
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous rootstocks improve yields and increase fruit sizes in grafted fresh market tomatoes

Abstract: Grafting high yielding tomato cultivars (Solanum lycopersicum L.) onto vigorous rootstocks can increase marketable yields, but questions remain regarding optimal cultural and growing conditions such as pinching and plant spacing. This study addressed some of the dynamics between grafted plants and cultural practices. Two scions, ‘Tasti-Lee’ (TL) and ‘Mountain Fresh Plus’ (MFP) were grafted onto each of three rootstocks, ‘Beaufort’, ‘Arnold’, and ‘Shield’. Plants were pinched (removal of main shoot to induce bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…For example, in 2022 the scion 'BHN 871' had higher yields of large fruit when grafted onto 'Fortamino', whereas 'Big Beef' had higher yields of large fruit when grafted onto 'DRO141TX'. Others who have examined scionrootstock interactions in tomato have found effects on fruit yield (Mauro et al 2020), fruit count (Gong et al 2022a) fruit quality (Gong et al 2022b;Mauro et al 2020) (Ingram et al 2022;Mauro et al 2020). However, others have found no evidence of interactions between rootstocks and scions in terms of their effect on yield (Gong et al 2022a;Ingram et al 2022).…”
Section: Rootstockmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in 2022 the scion 'BHN 871' had higher yields of large fruit when grafted onto 'Fortamino', whereas 'Big Beef' had higher yields of large fruit when grafted onto 'DRO141TX'. Others who have examined scionrootstock interactions in tomato have found effects on fruit yield (Mauro et al 2020), fruit count (Gong et al 2022a) fruit quality (Gong et al 2022b;Mauro et al 2020) (Ingram et al 2022;Mauro et al 2020). However, others have found no evidence of interactions between rootstocks and scions in terms of their effect on yield (Gong et al 2022a;Ingram et al 2022).…”
Section: Rootstockmentioning
confidence: 99%
“…Others who have examined scionrootstock interactions in tomato have found effects on fruit yield (Mauro et al 2020), fruit count (Gong et al 2022a) fruit quality (Gong et al 2022b;Mauro et al 2020) (Ingram et al 2022;Mauro et al 2020). However, others have found no evidence of interactions between rootstocks and scions in terms of their effect on yield (Gong et al 2022a;Ingram et al 2022). It should be noted that all of these studies were conducted with irrigation supplied.…”
Section: Rootstockmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that both the Suzuka and Kaiser rootstocks were better adapted to the greenhouse microclimatic conditions and responded better to the adopted cultivation practice than Top Bental, fully expressing their productive potential. Several authors have suggested that grafting tomato plants onto vigorous rootstocks improves fruit yield [46][47][48]. An increased efficiency of nutrient and water use, as a result of more vigorous root system development [49,50], was reported to play an important role in promoting the yield of grafted plants.…”
Section: Yield-related Traitsmentioning
confidence: 99%
“…Grafting connects the rootstock to the scion and involves cutting cells at the incision site and allowing new tissues to merge, forming new plants [10][11][12]. This technique is crucial for fruit tree breeding because it directly affects the growth, yield, and quality of various fruit trees, such as Prunus armeniaca L. [13], plum trees [14], and apple trees [15].…”
Section: Introductionmentioning
confidence: 99%